2011
DOI: 10.1128/cvi.05021-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Varicella Vaccines and Varicella-Zoster Virus from Vaccine-Related Skin Lesions

Abstract: To prevent complications that might follow an infection with varicella-zoster virus (VZV), the live attenuated Oka strain (V-Oka) is administered to children in many developed countries. Three vaccine brands (Varivax from Sanofi Pasteur MSD; Varilrix and Priorix-Tetra, both from Glaxo-Smith-Kline) are licensed in Germany and have been associated with both different degrees of vaccine effectiveness and adverse effects. To identify genetic variants in the vaccines that might contribute to rash-associated syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…Some studies have reported that vOka genotypes in rash vesicles are monomorphic but that different vesicles in the same individual harbor different genotypes . Others have found that individual vesicles contain multiple genotypes . Despite the discrepancies, these findings highlight that rashes are not caused by a single vOka haplotype from the vaccine.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies have reported that vOka genotypes in rash vesicles are monomorphic but that different vesicles in the same individual harbor different genotypes . Others have found that individual vesicles contain multiple genotypes . Despite the discrepancies, these findings highlight that rashes are not caused by a single vOka haplotype from the vaccine.…”
Section: Introductionmentioning
confidence: 92%
“…Over 90% of these were present on less than 10% of genomes and would therefore have been missed by traditional Sanger methods used for previous whole‐genome sequencing of vOka preparations . In addition to differences in the sequence of the three commercial vaccine preparations, variation has also been reported in the genetic composition of Varilrix when compared with Varivax (Table ). There is evidence to suggest that such differences affect immunogenicity of the vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Wirksamkeit nach 1 Impfung wurde dabei auch impfstoffspezifisch in Ausbrüchen untersucht, wobei sich Hinweise auf Unterschiede zwischen den in Deutschland verwendeten Impfstoffen ergaben [19]. Diese Ergebnisse korrespondierten mit der bei der Nukleinsäuren-Sequenzanalyse gefundenen genetischen Mikroheterogenität der Impfviren der in Deutschland verwendeten Varizellenlebendimpfstoffe [29,30]. Weitere Untersuchungen sind jedoch nötig, um die klinische Relevanz dieser Ergebnisse genauer zu bestimmen und um die impfstoffspezifische Wirksamkeit von 2 Impfungen im Ausbruchsfall zu ermitteln.…”
Section: Diskussionunclassified
“…They are more sensitive than viral cultures, DFA and Tzanck smears particularly when primers for genes 28 and 29 are used [30,428,429,440,449,450,457] . Molecular biology tests are also useful in the case of varicella appearing 7-42 d after vaccination, in the case of herpes zoster appearing 42 d after vaccination and, in the case of the suspected transmission of the vaccine virus, can distinguish virus vaccine, wild-type virus and potential recombinants of vaccine and wild-type viruses [30,451,452,454,455,[458][459][460][461][462][463] , although some tests have proved to be less appropriate over time for these purposes [30] . There are also some multiplex assays that can differentiate HSV-1, HSV-2 and VZV in cutaneous and mucocutaneous samples, making them very useful in the case of skin lesions of unclear etiology or immunosuppressed patients [429,464,465] .…”
Section: Direct Fluorescent Antibody Assaymentioning
confidence: 99%